2009
DOI: 10.1115/1.2871105
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy and Convergence Using a Local Interaction Simulation Approach in One, Two, and Three Dimensions

Abstract: Guided waves are utilized in structural health monitoring for identifying damage in material components. Simulations can be used to examine how elastic waves propagate in components to help in selecting measurement and data analysis techniques. In this work, the influence of grid size and the frequency sample rate on the amplitude accuracy and convergence of local interaction simulation approach/sharp interface model (LISA/SIM) numerical simulations are studied as they pertain to guided wave propagation in str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Previous researchers 20 have noted the dependence of LISA results on the in-plane discretization. This dependence is also seen in the present LISA Hybrid results, particularly in the group velocity of the propagating wave.…”
Section: Ivb Effect Of In-plane Discretizationmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous researchers 20 have noted the dependence of LISA results on the in-plane discretization. This dependence is also seen in the present LISA Hybrid results, particularly in the group velocity of the propagating wave.…”
Section: Ivb Effect Of In-plane Discretizationmentioning
confidence: 96%
“…Sundararaman and Adams used a three-dimensional LISA formulation to study the effect of simple damage in isotropic and unidirectional orthotropic plates 9 and subsequently examined the effects of grid size. 20 Recently, Nadella and Cesnik 15, 21 extended the approach to simulate wave propagation in arbitrary composite laminates and expanded the 3-D formulation to account for plies in non-principal directions. The resulting iterative equations are used in this work, and they are included for reference in the appendix.…”
Section: Iiia Theoretical Developmentmentioning
confidence: 99%
“…The parameters (cuboid grid and time step) used in the discretization of the Eqs. (11)- (13) are selected based on the Courant-Friedric-Lewy (CFL) criterion. The CFL criterion is a constraint that bounds the time step and cell size by the relation:…”
Section: Displacement and Stress Continuitymentioning
confidence: 99%
“…Traditional numerical tools such as finite elements (FE) are computationally inefficient because of the small wavelength discretizations required to attain converging results. It has been shown that local interaction simulation approach (LISA) [9,10], a numerical method based on finite difference (FD) transformations is capable of efficiently and accurately modeling GW propagation. This method is based on iterative equations (IE) for "unit cells" that are used to represent/discretize the model.…”
Section: Introductionmentioning
confidence: 99%
“…LISA employs the sharp interface model (SIM) to address the issue of discontinuities and boundaries, which distinguishes it from the formal FD techniques. LISA has been used to study the wave propagation characteristics [11] [12] and accuracy of simulations [10] in isotropic plates. Furthermore, damage interaction and identification [13] also addressed in 2-D isotropic plates.…”
Section: Introductionmentioning
confidence: 99%